Mycobacterium avium subsp. paratuberculosis in bovine faeces from the municipality of Sincelejo, Sucre, Colombia - Caraballo Blanco, Libardo (2018)
The objective of the study was to determine the presence of Mycobacterium avium subsp. paratuberculosis (MAP) in cattle faeces from the municipality of Sincelejo, Sucre, Colombia. A direct bacteriological study was performed by microscopy techniques and polymerase chain reaction (PCR) for pools of faeces with two molecular markers, one specific for MAP (IS900) and another based on 16S of the genus Mycobacterium. The presence of acid-fast bacilli occurred in 21.1% of the faecal samples stained with Ziehl Neelsen. Three pools were positive with IS900 and three with 16S. The sequencing indicated the presence of three species of bacteria: MAP, Mycobacterium abscessus and Dietzia timorensis. The presence of MAP in the department of Sucre is identified for the first time.